Dehydrogenation kinetics and reversibility of LiAlH4–LiBH4 doped with Ti-based additives and MWCNT. (November 2016) - Thaweelap, Natthaporn; Utke, Rapee
Abstract: Dehydrogenation kinetics and reversibility of LiAlH4 –LiBH4 doped with Ti-based additives (TiCl3 and Ti-isopropoxide), multiwall carbon nanotubes (MWCNT), and MWCNT impregnated with Ti-based additives are proposed. Reduction of dehydrogenation temperature as well as improvements of kinetics and reversibility, especially decomposition of thermodynamically stable hydride (LiBH4 ) is obtained from the samples doped with Ti-isopropoxide and MWCNT. This can be due to the fact that the formations of Li x Al(1− x ) B2 and LiH-Al containing phase during dehydrogenation favor decomposition of LiH, leading to increment of hydrogen capacity, and stabilization of boron in solid state, resulting in improvement of reversibility. Besides, the curvatures and thermal conductivity of MWCNT benefit hydrogen diffusion and heat transfer during de/rehydrogenation. Nevertheless, deficient hydrogen content reversible is observed in all samples due to the irreversible of LiAlH4 and/or Li3 AlH6 as well as the formation of stable phase (Li2 B12 H12 ) during de/rehydrogenation. Highlights: Kinetic improvement of LiAlH4-LiBH4 by doping with Ti-based additives and MWCNT. Significant reduction of dehydrogenation temperature (Δ T up to 40 °C). Faster desorption of thermally stable phase of LiBH4 (from 2.7 to up to 4.7 wt% H2). Increase of H2 content reversible from 2.8 to up to 3.7 wt%.